Insider trading: a punição da vantagem indevida pela conduta - Figueiredo, Leonardo Weiler (2022)
The objective of the work developed here will be to situate, develop, discuss, and seek a solution to this problem as well as to address the question, why so much occurrence when we deal with this issue. Expose and stress cases that have and have not been resolved, bring court decisions on previous situations seen in the legal framework. A very important point will be, how can Brazilian compliance act in this movement? What points seen abroad? What remedy can be used for this epidemic? The nature of this project is to better understand the problem, identify it and understand the motivation for its continuation, as it is frequently seen on the national scene. The purpose is to expose and better present the subject, which is often treated as general knowledge, when in fact it is very little explored. The macro-objective is to deal with the subject, also bringing it into the everyday context. Analyze issues that have already been judged, evaluate situations that have already been seen and raise questions. In summary, the present takes place to indicate how the repression of insider trading in the Brazilian scenario can be improved, not only presenting the current aspects and mechanisms for this, but also suggesting and evaluating new ways of rebutting such conduct. The relevance of the theme for the capital market is almost extreme. If we judge the impact of this practice in the current scenario as well as in the history of Brazilian commercial law, there is a clear urgency to treat this issue more seriously. The body that deals with the matter in Brazil is the Securities and Exchange Commission - CVM, which, even having mechanisms to defend such conduct, still sees it in the market. Once this topic is better exposed, it will be possible to observe suggestions to provide answers to the aforementioned problem. The possibility of a clear change in the scope of the reality of the capital market is something very relevant, since this is one of the most relevant sectors in the world in terms of revenue. In view of the above, it is also worth mentioning that, although in an environment outside Brazil the subject is treated with greater recurrence and attention, in the daily reality of the national Capital Market it is not possible to notice such a vision. Even though this topic has never been ignored, there is still a lot to deal with